Psycho-pedagogical strategy to enhance intrinsic motivation towards learning Karate-do (Original) (Revista científica Olimpia, 2020)
This research was carried out in the EIDE Captain Orestes Acosta of Santiago de Cuba in the sport of karate do, with the aim of developing a psycho-pedagogical strategy to sensitize trainers, athletes and others involved in the importance of intrinsic motivation for teaching-learning process of the same. For the study, methods and techniques were applied such as: observation, semi-structured interview and surveys. The qualitative analysis of the results indicates that coaches have inadequacies in the domain of participatory methodologies and in the conception and instrumentation of teaching methods, and in athletes the need to improve their teaching-learning processes predominates, wishing to develop effective strategies that favor an integral formation. The proposed psycho-pedagogical strategy is based on epistemological, theoretical, methodological and didactic foundations that support its instrumentation and is made up of three stages with its corresponding actions. The aspects analyzed by the experts, both of the specific actions, and of the strategy as a whole, achieved positive assessments that validate the design for its subsequent implementation. The implementation of this psycho-pedagogical can be a good working instrument, to optimize the type of interactions that are maintained between athletes and coaches in said center and to promote the development of intrinsic motivation towards learning karate do.
Keywords: intrinsic motivation; karate do; psycho-pedagogical strategy; teaching-learning